2017
DOI: 10.1002/stem.2572
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Biphasic Role of Calcineurin/NFAT Signaling Enables Replacement of Sox2 in Somatic Cell Reprogramming

Abstract: Induction of pluripotency with defined factors (octamer-binding transcription factor 4 [Oct4], SRY (sex determining region Y)-box 2 [Sox2], Kruppel-like factor 4 [Klf4], c-Myc) raises hopes for successful clinical trials. Despite considerable efforts, the molecular mechanism of reprogramming remains poorly understood. The aim of the present study was to identify the role of calcineurin/nuclear factor of activated T cells (NFAT) in reprogramming. Our results demonstrated a biphasic role for calcineurin/NFAT sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
3
4
2
Order By: Relevance
“…In line with the reported biphasic role of NFATC2 on cellular preprogramming (Khodeer & Era, 2017, Sun, Liao et al, 2016, Nfatc2 transcripts were slightly induced during reprogramming in wild-type cells ( Figure 4A). These transcripts were repressed in Cola1(miR-203) cells and dramatically upregulated in miR-203(/) cells at intermediate stages during reprogramming to be finally silenced in stable iPS clones ( Figure 4A).…”
Section: Nfatc2 Is a Critical Target Of Mir-203 Effects During Reprogsupporting
confidence: 87%
See 3 more Smart Citations
“…In line with the reported biphasic role of NFATC2 on cellular preprogramming (Khodeer & Era, 2017, Sun, Liao et al, 2016, Nfatc2 transcripts were slightly induced during reprogramming in wild-type cells ( Figure 4A). These transcripts were repressed in Cola1(miR-203) cells and dramatically upregulated in miR-203(/) cells at intermediate stages during reprogramming to be finally silenced in stable iPS clones ( Figure 4A).…”
Section: Nfatc2 Is a Critical Target Of Mir-203 Effects During Reprogsupporting
confidence: 87%
“…These transcripts were repressed in Cola1(miR-203) cells and dramatically upregulated in miR-203(/) cells at intermediate stages during reprogramming to be finally silenced in stable iPS clones ( Figure 4A). At the protein level, NFATC2 was induced by day 5 in wild-type cells as reported previously (Khodeer & Era, 2017, Sun et al, 2016, and this induction was enhanced in miR-203 knock-out cells ( Figure 4B). Members of the NFAT transcription factor family, including NFATC2, are normally present in the cytoplasm in a hyperphosphorylated and inactive form.…”
Section: Nfatc2 Is a Critical Target Of Mir-203 Effects During Reprogsupporting
confidence: 85%
See 2 more Smart Citations
“…A previous study of our laboratory has shown that calcineurin‐NFAT signaling plays a critical role in regulating early lineage specification of mouse ESCs, through controlling Src expression and the epithelial–mesenchymal transition (EMT) process (X. Li, Zhu, et al, 2011). Moreover, it was later reported that calcineurin‐NFAT signaling also functioned in somatic cell reprogramming (Khodeer & Era, 2017; Sun et al, 2016). However, the function of calcineurin‐NFAT signaling in hESCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%